A formula for the Bohl exponent of discrete time-varying systems. (January 2023) - Czornik, Adam
Abstract: In this note, a formula for the Bohl exponent of a discrete system with slowly varying coefficients was proved. This formula expresses the Bohl exponent through the eigenvalues of the coefficients. Based on these formulae a necessary and sufficient condition for uniform exponential stability of such systems are also presented.